Clinical correlation of cardiac functions and troponin I and CPK-MB in dengue fever in children - Chaudhary, Devanand G.; Srinivasan, Shyam; Sutay, Nita R. (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue is the most rapidly spreading mosquito-borne viral disease in the World. The spectrum of manifestations includes mild fever to severe and life-threatening disease, though uncommon complications such as myocarditis have also been reported in many cases. We conducted this study to analyze association between Clinical Profile, Cardiac Functions and Troponin I and CPK-MB (cardiac biochemical markers) in children with Dengue Fever. Aims and objectives of the study was the association between Clinical Profile, Cardiac Functions and Troponin I and CPK-MB (cardiac biochemical markers) in children with Dengue Fever. Methods: This was a prospective observational study in which 80 paediatric patients who were hospitalized and diagnosed to be having Dengue fever were included. All patients were stratified into either of the 3 groups- Dengue without warning signs, Dengue with warning signs and severe Dengue. A detailed history and thorough clinical examination were done for all patients. A complete blood count, electrolytes, hepatic and renal function tests were done in all children. Cardiac function was assessed by 2D Echo, CPK-MB and Troponin-I, p value less than 0.05 was taken as statistically significant. Results: Of the 80 studied cases there were 53 (66.25%) males and 27 (33.75%) females with a M:F ratio of 1.9:1. Dengue with and without warning signs was seen in 27.5% and 60% cases respectively whereas severe dengue was seen in 12.5% cases. The ejection fraction was comparable across the 3 groups. On 2D echo ejection fraction was 62.95%, 63.21% and 65.1% in cases with warning signs, without warning signs and severe dengue respectively. Additionally, ECG abnormalities were seen in 8.75% patients. All 80 patients had a normal CPK-MB and Troponin-I levels. Conclusions: Cardiac markers (CPK-MB and Troponin-I) remain unaffected during Dengue illness and do not have significant correlation between Dengue without warning signs, Dengue with warning signs and severe Dengue.